The psychology of unethical behavior in the finance industry - PITESA, Marko (Institutional Knowledge at Singapore Management University, 2015)
The finance industry has been singled out as a case of rampant unethical behavior and corporate greed. Drawing on scientific research on unethical behavior from the disciplines of psychology, behavioral ethics, behavioral economics, and organizational behavior, I discuss three characteristics of the finance industry that might explain the high level of unethical behavior in this domain of work. I review research explaining how the disproportionate representation of power and wealth might affect how people working in finance approach social relationships, with important consequences for their propensity to behave unethically. Next, I review the literature suggesting that competitive and demanding work environments that characterise many domains of finance affect the likelihood of unethical behavior both directly and through their effect on employees’ level of available self-regulatory resources. I also argue that the finance industry is marked by a low saliency of those affected by unethical actions and a low sense of personal agency in unethical behavior, and present work showing these factors that may prompt and license unethical conduct. Finally, I discuss how the understanding of the characteristics of the finance industry that contribute to the high level of unethical behavior in this domain may inform decision makers in regulating and managing unethical behavior in finance.